1987
DOI: 10.1002/1098-108x(198703)6:2<199::aid-eat2260060205>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of psychosexual factors in the causation of eating disorders: Time for a reappraisal

Abstract: The role of sexual identity has been of interest to many workers in the field of anorexia nervosa and related disorders. In particular it has long been suggested that psychosexual factors play a contributory part in the development of eating disorders. This article addresses itself to (1) examples of psychoanalytical perspectives, (2) some empirical findings and associated theoretical frameworks, (3) evidence from sex role inventories, and (4) psychosexual factors within male anorexics. It is concluded that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In addition to the findings discussed, some researchers have been unable to reveal any sex role orientation or sex role ideology differences between women with and without eating disorders (Beren & Chrisler, 1990;Scott, 1987;Xinaris & Boland, 1989). Others have argued that any type of gender-role typing (whether masculine or feminine) is related to eating disorder (Thornton et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to the findings discussed, some researchers have been unable to reveal any sex role orientation or sex role ideology differences between women with and without eating disorders (Beren & Chrisler, 1990;Scott, 1987;Xinaris & Boland, 1989). Others have argued that any type of gender-role typing (whether masculine or feminine) is related to eating disorder (Thornton et al, 1991).…”
Section: Discussionmentioning
confidence: 94%
“…Femininity has been found to receive higher endorsement among women with bulimia than among women with no eating disorders (Holleran, Pascale, & Fraley, 1988;Scott, 1987;Szymanski & Chrisler, 1990). Some researchers have therefore concluded that hyperfemininity is a trait among women with eating disorders (Steiger, Fraenkel, & Leichner, 1989).…”
Section: Femininitymentioning
confidence: 99%
“…However, other papers have taken issue with this and claim there is a variety or little' evidence for disturbed psychosexual function in eating-disordered. patients (20,21). Part of this confusion may stem from a failure to distinguish between patients with anorexia nervosa and those with bulimia nervosa.…”
Section: Sexualitymentioning
confidence: 99%
“…Russell (1979) and Garfinkel and Garner (1982) stated that bulimics were more sexually active and experienced than restricting anorexics. Scott (1987) concluded that many beliefs as noted above find little basis in the few empirical studies done to date.…”
mentioning
confidence: 98%